UNVEILING MORPHOSYNTACTIC PATTERNS IN SUBTITLES FOR DEAF AND HARD-OF-HEARING VIEWERS IN “A QUIET PLACE” - Intan Mustika Sari (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2025)
Subtitles for the Deaf and Hard-of-Hearing (henceforth SDH) are key to guaranteeing equal access to audio-visual media content for hearing-impaired viewers. In this study, the authors analysed morphological forms and affixations used in the movie A Quiet Place directed by John Krasinski in 2018 to see how much the inflectional and derivational characteristics, parts of speech, collocation patterns, and clause patterns play a role in creating a successful SDH. This study is significant as it addresses a missing link in SDH research, such as the morphological structure of SDH, specifically affixation, affects readability, access, and logical flow of Subtitles for the Deaf and Hard of Hearing. The linguistic representation of SDH, with its capacity to be used as an aide for viewers’ comprehension, may therefore be appreciated under the spirit of inclusive media. The study addresses the types of queries that are the largest on certain morphological forms in sound-based filming and how these amounts can help readers understand the narrative. In this study, SDH components were subjected to comparison, organization, and trimming in order to determine the expressions of types and frequency of affixation, their distribution across word lexical categories, and syntax co-occurrence. Data were collected through a close analysis of the SDH script, which was tagged for inflectional and derivational morphemes, clause types, and collocational alternatives. Lexington Functional Grammar’s (henceforth LFG) structural appurtenance underlies the morphological process of how language contributes to SDH, compositionally focusing on understandability and easier access for the Deaf and Hard-of-Hearing audiences. Compared with derivational forms, the results show a preponderancy of inflectional affixation (196 instances) of suffixes -ing, -ed, and -s. In addition, 166 SDH items were included in terms of sound, and a great number of them were concrete nouns, which helped to establish situational comprehension. Simple clauses (81 cases) and noun+verb phrases (60 cases) were common, suggesting a less subtle direction for cognitive simplification. This study shows the idea that conscientious linguistic decisions (e.g., preference in inflectional suffixes and syntactic complexity reduction) can enhance the narrative experience of Deaf and Hard-of-Hearing viewers. It also contributes to the linguistics theory that morphosyntactic simplification, ellipsis, and restructuring cross cut principles of economy and audio-visual translation by covering the linguistic form corresponding to filmic silence as well as to aural and visual representation.